IMPLEMENTASI METODE CRM OPERASIONAL PADA SISTEM INFORMASI PEMESANAN MAKANAN DI KABUPATEN KUNINGAN BERBASIS ANDROID - Mochamad Anggi Zaelani; Sugeng Supriyadi; Rio Andriyat Krisdiawan (Cloud Information, 2018)
Marketplace is an online sales system in which there are buyers and sellers who are usually used by businessmen to market their products or services, because they are considered more effective and efficient. The system that will be created will produce an online market in which there are food products from various different restaurants. This system implements an operational Customer Relationship Management (CRM) method to establish good relationships with existing customers and to obtain new customers. This system is based on Android and it is built with the Java programming language, MySQL database as a data storage and testing methods using white boxe and black box texting. Entities involved in this system are customers, sellers and admin. The seller can manage the data including food data, discount, sales data, send orders and withdrawal of sales balance. While the admin can confirm the request for withdrawal of balance and manage user data that is deleting user data if there is a request or there are other problems. Customers who want to order food must first be registered in the system, then make payments via bank transfer and after that confirm the orders that have been paid. Then the delivery of orders is done by the seller with the provision for a minimum purchase of several portions for locations very far from the seller. Customers who have already registered in the application can see information in the form of food discounts, foods that are most favored by buyers and the latest products marketed by sellers.